AUGMENTED REALITY (AR)-BASED LEARNING ON PHYSICAL EDUCATION LEARNING OUTCOMES - Rizkei Kurniawan; Sultan Maulana Hakim; Yoki Afriandy Rangkuti; Didi Yudha Pranata (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2025)
This study aims to evaluate the effectiveness of Augmented Reality (AR)-based learning in improving physical education outcomes among junior high school students. Using a quantitative approach with a pretest–posttest design, the research involved 32 students who received AR-assisted instruction on basic basketball movements. The assessment instruments covered cognitive, affective, and psychomotor domains. The findings revealed a significant improvement from pretest to posttest scores, with the N-Gain value categorized as effective. The use of AR provided an immersive learning experience through three-dimensional visualization, enhancing students’ motivation, engagement, and conceptual understanding. The discussion highlights that AR supports active learning in line with constructivist and socioconstructivist theories, while also offering opportunities to strengthen motor skills through interactive simulations. Nevertheless, the implementation of AR still faces challenges such as limited teacher competence and technological infrastructure. These findings underscore the potential of AR as an innovative learning medium to improve the quality of physical education. The implications of this study include the need for teacher training and the development of adaptive technology-based learning models.